Gender-dependent and age-of-onset-specific association of the rs11675434 single-nucleotide polymorphism near TPO with susceptibility to Graves’ ophthalmopathy - Kuś, Aleksander; Szymański, Konrad; Jurecka-Lubieniecka, Beata; Pawlak-Adamska, Edyta; Kula, Dorota; Miśkiewicz, Piotr; Bolanowski, Marek; Płoski, Rafał; Bossowski, Artur; Daroszewski, Jacek; Jarząb, Barbara; Bednarczuk, Tomasz (Journal of human genetics, 2017)
The role of TPO gene polymorphism in the susceptibility to Graves' disease (GD) remains unclear. However, single-nucleotide polymorphisms (SNPs) near TPO have been recently associated with serum levels of thyroid peroxidase (TPO) antibody in two independent genome-wide association studies. Moreover, we have observed a strong association between the rs11675434 SNP located near TPO and the presence of clinically evident Graves' ophthalmopathy (GO). The aim of the current study was to reevaluate and dissect this association in an extended group of 1231 well-characterized patients with GD (1043 adults and 188 children) and 1130 healthy controls from the Polish Caucasian population, considering possible gender-dependent and age-of-onset-specific effects of the studied SNP. We found that the T allele of rs11675434 was significantly more frequent in GD patients with than without GO (odds ratio (OR)=1.26, 95% confidence interval (CI)=1.05-1.51, P=0.012), which was consistent with our previous findings. Further analyses performed in subgroups of patients showed that the association with GO was significant in adult patients with age of GD onset ⩾45 years (OR=1.34, 95% CI=1.03-1.75, P=0.031), but not in children and adolescents or adult patients with earlier onset of the disease (OR=1.72, 95% CI=0.77-3.84, P=0.18 and OR=1.05, 95% CI=0.79-1.40, P=0.75, respectively). Moreover, a strong association with GO was present in males (OR=2.06, 95% CI=1.40-3.02, P=0.0002), whereas it was absent in females (OR=1.10, 95% CI=0.90-1.35, P=0.35). The results of our study further suggest that rs11675434 SNP located near TPO is associated with the development of GO, especially in males and patients with later age of GD onset.